Examining the State of Accreditation for Engineering Programs in India: Insights, Challenges and Future Directions - Gupta, Ankur; Sawhney, Sahil; Gupta, Adit (Journal of Engineering Education Transformations, 2025)
The National Board of Accreditation (NBA) offers program level accreditation for the higher technical education space in India. Accreditation by the NBA is a mandatory requirement for program-level expansion and the initiation of new programs. The All-India Council for Technical Education (AICTE) mandates that all institutions must have 60 percent of their eligible programs accredited by the NBA to receive approval to operate beyond 2024. Given the necessity for institutions to have their programs accredited by the NBA, it would be expected that many institutions would have completed the accreditation process. However, an analysis of the penetration of NBA accreditation across India based on several parameters indicates otherwise. In this paper, we examine the potential reasons for the low penetration of NBA accreditation across institutions and suggest measures to improve the penetration of program-level accreditation moving forward.